Method for constructing microwave absorbing material by loading metal phthalocyanine on MXene

By introducing metal phthalocyanine into MXene absorbing materials and performing axial coordination, the problems of self-aggregation and easy oxidation of MXene absorbing materials are solved, and high-performance electromagnetic wave absorbing materials are achieved, with multiple loss mechanisms and adjustable frequency absorption performance.

CN119560802AActive Publication Date: 2025-03-04BEIHANG UNIV
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411823519.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-04
Estimated Expiration
2044-12-11

AI Technical Summary

Technical Problem

The existing MXene absorbing materials have problems such as self-aggregation, easy oxidation, single loss mechanism and easy impedance mismatch, which limits their absorbing performance and practical applications.

Method used

By axial coordination of the functionalized MXene and metal phthalocyanine, the MXene-metal phthalocyanine composite material was prepared by self-assembly method, the impedance matching was optimized and a multi-heterogeneous interface was constructed to enhance the electromagnetic wave attenuation capability.

Benefits of technology

It realizes the high-performance preparation of MXene wave absorbing materials, has multiple loss mechanisms and adjustable frequency absorbing performance, and is suitable for electromagnetic wave absorption field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005183654670000011
    Figure HDA0005183654670000011
  • Figure HDA0005183654670000012
    Figure HDA0005183654670000012
  • Figure HDA0005183654670000021
    Figure HDA0005183654670000021
Patent Text Reader

Abstract

The invention discloses a method for constructing a microwave absorbing material by loading metal phthalocyanine on MXene, and belongs to the field of wave absorbing materials. MXene is used for loading metal phthalocyanine, a heterostructure is constructed, impedance matching is optimized, the MXene-metal phthalocyanine composite material is prepared, and application of the MXene-metal phthalocyanine composite material in the field of wave absorption is achieved. The method for preparing the MXene-metal phthalocyanine composite material comprises the following steps: (1) adopting an ultrasonic dispersion method to obtain a uniform solution of MXene and metal phthalocyanine; and (2) putting the uniform solution into a wide-mouth bottle by adopting a liquid-phase ultrasonic self-assembly method, and reacting to obtain the MXene-metal phthalocyanine composite material. The metal phthalocyanine is introduced on the surface and between layers of MXene, the impedance matching characteristic of MXene is optimized, the electromagnetic wave absorption performance and the effective absorption frequency band are effectively regulated and controlled, and then the broadband, light-weight, efficient and adjustable wave-absorbing material can be prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a type of MXene-loaded phthalocyanine composite material prepared by a self-assembly method and its application in the field of wave absorption. Background Art

[0002] As the latest progress in the field of wireless communications, 5G technology has achieved rapid development in various fields such as the Internet of Things, smart cities, and aerospace. It has greatly improved people's lives and provided higher efficiency and convenience. However, in addition to the many potential advantages of 5G technology, the accompanying electromagnetic radiation and electromagnetic wave pollution problems also need to continue to be paid attention to and studied. A large number of studies have shown that long-term exposure to electronic warfare pollution can easily cause catastrophic diseases such as leukemia and tumors, posing a serious threat to human health; electronic equipment is also likely to be subject to electromagnetic interference from other equipment, seriously affecting the accuracy and stability of data and signals. Therefore, both human health and the smooth operation of electronic equipment have an urgent need to reduce electromagnetic hazards, and the design and development of electromagnetic wave absorbing materials (i.e., absorbing materials) provide a solution for this.

[0003] As a new type of two-dimensional material, MXene has shown good application prospects in the fields of wireless communication, energy storage and conversion, electromagnetic wave absorption and electromagnetic interference shielding. MXene has abundant hydrophilic functional groups (-O and -OH), excellent mechanical properties, good electrical properties and chemically active surfaces, so it has great value in the field of electromagnetic wave absorption and is a candidate material for preparing "thin, light, wide and strong" absorbing materials. However, the original MXene absorber has a series of problems, such as self-aggregation, easy oxidation, single loss mechanism and easy impedance mismatch, which greatly limit its absorbing performance and practical application.

[0004] In order to further improve the MXene's absorbing performance and environmental adaptability, MXene-based absorbing materials obtained through composition and structural design have been widely used. Reasonable composition optimization can bring richer synergistic loss mechanisms, stronger polarization loss capabilities, and achieve impedance matching of MXene-based absorbing materials. By utilizing the synergistic advantages between the components of the composite material, the multifunctionality of MXene-based materials can also be achieved, such as thermal insulation, hydrophobicity, corrosion resistance, etc., which greatly enhances the scope of application in practical environments. In addition, by constructing a three-dimensional hierarchical structure through structural design, the expansion of the multi-dimensional unit coupling scale can enhance the attenuation capacity, providing a feasible way to prepare ultra-light density and ultra-low filling rate MXene-based absorbing materials. However, how to select a suitable filler material for compounding with the MXene matrix, while ensuring the absorbing performance and having the characteristics of easy preparation and low cost, is still a problem that needs to be solved urgently. Summary of the invention

[0005] The present invention is proposed based on the inventor's discovery of the following facts and problems:

[0006] Phthalocyanine is a synthetic compound with a unique 18-electron extended conjugated system. The central hydrogen atom can be replaced by a metal element, and chelates with the metal in the cavity through two covalent bonds and two coordination bonds to form metal phthalocyanine. The electronic structure of phthalocyanine determines its special stability. The strong coupling inside phthalocyanine makes its benzene ring structure less likely to deform, and it has significant thermal and chemical stability. The presence of the central metal atom is more conducive to the stability of its properties. This stable conjugated structure leads to very strong absorption at 300-400nm (Soret band) and 700nm (Q band), which helps to build a multi-band absorption system. However, through π-π supramolecular interactions, these planar and highly conjugated aromatic macrocycles tend to spontaneously organize into stacks.

[0007] Furthermore, through in-depth research, the inventors found that metal phthalocyanine is easy to axially coordinate with other substances through the central metal, and this coordination can effectively prevent the stacking of phthalocyanine. MXene has abundant surface functional groups. By further functionalizing it, its surface groups can be axially coordinated with the central metal of metal phthalocyanine, improving the disadvantage of easy stacking. At the same time, a large number of heterogeneous interfaces can be constructed, which is conducive to electron hopping and enhanced electron transfer. Therefore, functionalizing MXene and axially coordinating it with metal phthalocyanine is one of the future development directions of high-performance electromagnetic wave absorption materials.

[0008] In view of this, in one aspect of the present invention, the technical problem solved by the present invention is to introduce metal phthalocyanine into the MXene-based absorbing material system in view of the deficiencies of the above-mentioned prior art, and provide a self-assembly method for preparing MXene-metal phthalocyanine composite materials and their applications in the field of absorbing waves. The process of this method is simple and reproducible, and the materials used are simple to synthesize, inexpensive, and easy to prepare on a large scale, which is conducive to the realization of materials and commercial applications. By adopting this method, unique metal phthalocyanine can be introduced between MXene layers and on the surface, bringing about multiple loss mechanisms, effectively optimizing the impedance matching of MXene, and then high-performance composite materials can be prepared and applied in the field of absorbing waves, especially to construct frequency-adjustable absorbing materials.

[0009] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for constructing an electromagnetic wave absorbing material by loading metal phthalocyanine with MXene and its application, the method is:

[0010] S1. Functionalization of MXene with alkaline solution

[0011] Preferably, the few-layer MXene is mixed with an alkaline solution to obtain an alkaline solution of MXene; the alkaline solution of MXene is stirred under an argon atmosphere, and then separated to obtain the functionalized MXene;

[0012] S2. The metal phthalocyanine powder is mixed with the first solvent and dispersed to obtain a dispersed metal phthalocyanine solution; the dispersed metal phthalocyanine solution is mixed with the functionalized MXene dispersion solution to obtain a uniform solution of MXene and metal phthalocyanine;

[0013] S3. The MXene and metal phthalocyanine homogeneous solution are ultrasonically mixed under an argon atmosphere, and a MXene-metal phthalocyanine composite solution is obtained by magnetic stirring reaction;

[0014] S4. Filter and wash the MXene-metal phthalocyanine composite solution, and dry it to obtain a composite material.

[0015] Preferably, the alkaline solution described in S1 is at least one of potassium hydroxide or sodium hydroxide; the concentration is 0.125-1.000 mol / L, preferably 0.5 mol / L, and the functionalization time is 2-12 h;

[0016] Preferably, the first solvent described in S2 is selected from DMF; the functionalized MXene dispersion solution uses the first solvent as a dispersion solvent;

[0017] Preferably, the metal phthalocyanine central metal described in S2 is one or more of Fe, Co, Ni, Cu, Zn, Mn, and Pb;

[0018] Preferably, in S2, the metal phthalocyanine solution is dispersed using ultrasound or a cell crusher, and the dispersion time is 10 to 60 minutes.

[0019] Preferably, the mass ratio of MXene to metal phthalocyanine in S2 is 1:1 to 1:9;

[0020] Preferably, in S3, the metal phthalocyanine solution is mixed with the MXene solution by dropwise addition, and the reaction is carried out at room temperature, with a magnetic stirring speed of 300 to 600 r / min and stirring for 10 to 30 h;

[0021] Preferably, in the MXene-metal phthalocyanine composite solution in S3, the mass percentage of MXene in the composite solution is 5% to 50%;

[0022] Preferably, in S4, centrifugal washing is performed at a speed of 3000 to 10000 rpm;

[0023] Preferably, the MXene-metal phthalocyanine composite material is used in the field of microwave absorption.

[0024] The MXene-metal phthalocyanine composite material and the matrix are compounded to prepare a microwave absorbing composite material, wherein the mass ratio of the MXene-metal phthalocyanine composite material to the matrix is ​​(0.1-0.4):1;

[0025] The matrix is ​​selected from at least one of paraffin, resin, and polyvinylidene fluoride;

[0026] The preparation method of the wave-absorbing composite material comprises the following steps:

[0027] (1) mixing the MXene-metal phthalocyanine composite material and the matrix in a predetermined ratio, dispersing them in an organic solvent, and ultrasonically mixing them to obtain a uniform solution; the organic solvent is at least one of N,N-dimethylformamide (DMF) and n-hexane;

[0028] (2) The mixed solution is transferred to a glass evaporating dish, and dried (preferably at 80° C.) to remove the solvent to obtain a uniformly dispersed composite film, and then the film is placed in a mold for hot pressing to obtain the absorbing composite material. The film thickness of the obtained composite material is in the mm level, such as 1-5 mm.

[0029] The MXene-metal phthalocyanine composite material obtained by the present invention and the matrix are compounded to prepare the wave absorbing composite material, and the wave absorbing frequency band can be regulated by regulating the dosage relationship of MXene-metal phthalocyanine, the dosage relationship of MXene-metal phthalocyanine composite material and matrix, and the thickness of the film (the wave absorbing frequency band generally regulated is in the range of 2-18 GHz). In this experiment, the effective absorption bandwidth of the MXene-metal phthalocyanine composite wave absorbing material based on the PVDF substrate is 0-4 GHz, and the reflection loss value is -10 to -60 dB.

[0030] In another aspect of the present invention, the present invention proposes a metal phthalocyanine-MXene composite material for electromagnetic wave absorption. According to an embodiment of the present invention, the metal phthalocyanine-MXene composite absorbing material is prepared by the method for preparing the metal phthalocyanine-MXene composite material of the above embodiment. Thus, in the metal phthalocyanine-MXene composite material, the metal phthalocyanine is combined with the axial coordination of the central metal and the MXene, and the skin effect is eliminated by the coupling of the high conductive material and the low conductive material, so as to improve the impedance matching of the composite material, which is conducive to the incidence of more electromagnetic waves, and at the same time, a large number of heterogeneous interfaces are generated, resulting in charge redistribution, macroscopic electric moment, and interface polarization. At the same time, due to the different work functions of metal phthalocyanine and MXene, it is easy to form a potential barrier at the interface after the two are coordinated. The presence of the potential barrier leads to a large interface resistance, which is conducive to the accumulation of charge in this area. When an external electromagnetic field acts on the material, the positive and negative charges at the interface are driven to form a local dipole, resulting in a change in charge density and the appearance of an electric dipole moment, and the electromagnetic wave energy is converted into heat energy through polarization behavior and dissipated. The composite material is used as an electromagnetic wave absorbing material, showing good reflection loss capability. The experimental results show that metal phthalocyanine-MXene composite materials can be used for future high-performance electromagnetic absorbing materials.

[0031] Compared with the prior art, the present invention has the following advantages:

[0032] The present invention prepares a MXene-metal phthalocyanine composite material by axially coordinating the functionalized few-layer MXene and metal phthalocyanine through a self-assembly method; by compounding two different materials, the impedance matching of the composite material can be improved, a large number of heterogeneous interfaces can be formed, and the polarization behavior can be induced by the potential barrier formed at the interface to enhance the electromagnetic wave attenuation ability of the composite material, thereby preparing a high-performance composite material and applying it to the field of wave absorption, especially to construct a frequency-adjustable wave absorption material. The process of the method is simple and repeatable, and the materials used are simple to synthesize, low in price, and easy to prepare on a large scale, which is conducive to the commercialization of materials and devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a SEM image of the functionalized few-layer MXene in the embodiment of the present invention.

[0034] Figure 2 These are SEM images of the few-layer MXene-loaded metal phthalocyanines in the embodiments of the present invention (a is CoPc, b is FePc, and c is CuPc).

[0035] Figure 3 This is a graph of the wave absorption performance of a MXene / CoPc (MXene to CoPc mass ratio is 1:4) composite material based on a PVDF polymer matrix prepared in Example 1 of the present invention.

[0036] Figure 4 This is a graph of the wave absorption performance of a MXene / CoPc (MXene to CoPc mass ratio is 1:2) composite material based on a PVDF polymer matrix prepared in Example 1 of the present invention.

[0037] Figure 5 This is a diagram of the wave absorption performance of a MXene / FePc (MXene to FePc mass ratio is 1:4) composite material based on a PVDF polymer matrix prepared in Example 2 of the present invention.

[0038] Figure 6 This is a diagram of the wave absorption performance of a MXene / FePc (MXene to FePc mass ratio is 1:2) composite material based on a PVDF polymer matrix prepared in Example 2 of the present invention.

[0039] Figure 7 This is a diagram of the wave absorption performance of a MXene / CuPc (MXene to CuPc mass ratio is 1:4) composite material based on a PVDF polymer matrix prepared in Example 3 of the present invention.

[0040] Figure 8 This is a diagram of the wave absorption performance of a MXene / CuPc (MXene to CuPc mass ratio is 1:2) composite material based on a PVDF polymer matrix prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0041] The present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments, but the present invention is not limited to the following embodiments.

[0042] Example 1

[0043] A MXene-loaded CoPc composite material is prepared based on a self-assembly method in this embodiment.

[0044] The method is:

[0045] S1. 0.4 g MXene powder was dissolved in 200 mL deionized water, 0.5 M NaOH solution was added, magnetic stirring was performed for 4 h, MXene was functionalized, and then solid-liquid separation was performed;

[0046] S2. When the mass ratio of MXene to CoPc is 1:4, 0.24 g of CoPc is dissolved in 240 mL of DMF, and dispersed by ultrasound or a cell crusher to obtain a CoPc solution; when the mass ratio of MXene to CoPc is 1:2, 0.28 g of CoPc is dissolved in 280 mL of DMF, and dispersed by ultrasound or a cell crusher to obtain a CoPc solution;

[0047] S3. When the mass ratio of MXene to CoPc is 1:4, 0.06 g of the functionalized MXene is dissolved in 60 mL of DMF, and the CoPc solution obtained in S2 is added dropwise to the MXene solution, and after ultrasonic dispersion, it is magnetically stirred for 20 hours under an argon atmosphere to obtain a uniform solution; when the mass ratio of MXene to CoPc is 1:2, 0.14 g of the functionalized MXene is dissolved in 140 mL of DMF, and the CoPc solution obtained in S2 is added dropwise to the MXene solution, and after ultrasonic dispersion, it is magnetically stirred for 20 hours under an argon atmosphere to obtain a uniform solution;

[0048] S4. The S3 solution is washed with DMF and deionized water, and freeze-dried to obtain a composite material.

[0049] The SEM image of the functionalized MXene prepared in step S1 of this embodiment is as follows: Figure 1 As shown in the figure, after the MXene is modified, the nanosheets curl and wrinkle to form a three-dimensional petal-like structure. Due to stacking, the size is further increased. This curling and stacking are beneficial to the construction of a conductive network.

[0050] The SEM image of the composite material prepared in step S4 of this embodiment is as follows: Figure 2 As shown in (a), MXene still retains the wrinkled morphology and larger size after functionalization, and CoPc is successfully loaded on MXene.

[0051] This embodiment also provides a composite material of the MXene loaded with CoPc and a polymer matrix prepared above. The obtained MXene-metal phthalocyanine composite material is used in a wave absorbing material: the MXene-metal phthalocyanine composite material and the matrix are mixed in a predetermined ratio, dispersed in an organic solvent, and ultrasonically mixed to obtain a uniform solution; the mixed solution is transferred to a glass evaporating dish, dried (preferably at 80°C) to remove the solvent to obtain a uniformly dispersed composite film, and then the film is placed in a mold for hot pressing to obtain the wave absorbing composite material. Its wave absorbing performance diagram is shown in FIG. Figure 3 and Figure 4 shown.

[0052] For composite materials with MXene-CoPc material (MXene to CoPc mass ratio of 1:4) as filler and PVDF as substrate:

[0053] (1) When the filling amount is 10wt% (the filling amount is the mass ratio of the MXene-metal phthalocyanine composite material to the matrix) and the corresponding thickness is 5.00mm, the minimum reflection loss is -12.24dB at 17.21GHz, and the effective absorption bandwidth is 1.22GHz; Figure 3It can be seen that its performance changes with the change of thickness;

[0054] (2) When the filling amount is 15wt% and the corresponding thickness is 5.00mm, the minimum reflection loss is -21.43dB at 14.96GHz, and the effective absorption bandwidth is 1.76GHz; Figure 3 It can be seen that its performance changes as the thickness changes;

[0055] (3) When the filling amount is 20wt% and the corresponding thickness is 3.00mm, the minimum reflection loss is -23.57dB at 7.28GHz, and the effective absorption bandwidth is 2.08GHz; Figure 3 It can be seen that as the thickness changes, the performance also changes.

[0056] For composite materials with MXene-CoPc material (MXene to CoPc mass ratio of 1:2) as filler and PVDF as substrate:

[0057] (1) When the filling amount is 10wt%, the corresponding thickness is 5.00mm, the minimum reflection loss is -22.30dB at 3.76GHz, and the effective absorption bandwidth is 1.52GHz; Figure 4 It can be seen that as the thickness changes, the performance also changes.

[0058] (2) When the filling amount is 15wt%, the corresponding thickness is 2.95mm, the minimum reflection loss is -53.16dB at 6.08GHz, and the effective absorption bandwidth is 1.52GHz; Figure 4 It can be seen that as the thickness changes, the performance also changes.

[0059] (3) When the filling amount is 20wt% and the corresponding thickness is 2.00mm, the minimum reflection loss is -20.49dB at 7.94GHz, and the effective absorption bandwidth is 1.13GHz; Figure 4 It can be seen that as the thickness changes, the performance also changes.

[0060] Example 2

[0061] A MXene-loaded FePc composite material is prepared based on a self-assembly method in this embodiment.

[0062] The method is:

[0063] S1. 0.4 g MXene powder was dissolved in 200 mL deionized water, 0.5 M NaOH solution was added, magnetic stirring was performed for 4 h, MXene was functionalized, and then solid-liquid separation was performed;

[0064] S2. When the mass ratio of MXene to FePc is 1:4, 0.24 g of FePc is dissolved in 240 mL of DMF, and dispersed by ultrasound or a cell crusher to obtain a FePc solution; when the mass ratio of MXene to FePc is 1:2, 0.28 g of FePc is dissolved in 280 mL of DMF, and dispersed by ultrasound or a cell crusher to obtain a FePc solution;

[0065] S3. When the mass ratio of MXene to FePc is 1:4, 0.06 g of the functionalized MXene is dissolved in 60 mL of DMF, and the FePc solution obtained in S2 is added dropwise to the MXene solution, and after ultrasonic dispersion, it is magnetically stirred for 20 h in an argon atmosphere to obtain a uniform solution; when the mass ratio of MXene to FePc is 1:2, 0.14 g of the functionalized MXene is dissolved in 140 mL of DMF, and the FePc solution obtained in S2 is added dropwise to the MXene solution, and after ultrasonic dispersion, it is magnetically stirred for 20 h in an argon atmosphere to obtain a uniform solution;

[0066] S4. The S3 solution is washed with DMF and deionized water, and freeze-dried to obtain a composite material.

[0067] The SEM image of the functionalized MXene prepared in step S1 of this embodiment is as follows: Figure 1 As shown in the figure, after the MXene is modified, the nanosheets curl and wrinkle to form a three-dimensional petal-like structure. Due to stacking, the size is further increased. This curling and stacking are beneficial to the construction of a conductive network.

[0068] The SEM image of the composite material prepared in step S4 of this embodiment is as follows: Figure 2 As shown in (b), MXene still retains the wrinkled morphology and larger size after functionalization, and FePc is successfully loaded on MXene.

[0069] This embodiment also provides a composite material of the MXene loaded with FePc and a polymer matrix prepared above. The obtained MXene-metal phthalocyanine composite material is used in a wave absorbing material: the MXene-metal phthalocyanine composite material and the matrix are mixed in a predetermined ratio, dispersed in an organic solvent, and ultrasonically mixed to obtain a uniform solution; the mixed solution is transferred to a glass evaporating dish, dried (preferably at 80°C) to remove the solvent to obtain a uniformly dispersed composite film, and then the film is placed in a mold for hot pressing to obtain the wave absorbing composite material. Its wave absorbing performance diagram is shown in FIG. Figure 5 and Figure 6 shown.

[0070] For composite materials with MXene-FePc material (MXene to FePc mass ratio of 1:4) as filler and PVDF as substrate:

[0071] (1) When the filling amount is 10wt% and the corresponding thickness is 2.00mm, the minimum reflection loss is -8.57dB at 17.20GHz, and the effective absorption bandwidth is 0.00GHz; Figure 5 It can be seen that its performance changes as the thickness changes;

[0072] (2) When the filling amount is 15wt% and the corresponding thickness is 3.00mm, the minimum reflection loss is -12.61dB at 11.92GHz, and the effective absorption bandwidth is 1.92GHz; Figure 5 It can be seen that its performance changes as the thickness changes;

[0073] (3) When the filling amount is 20wt% and the corresponding thickness is 5.00mm, the minimum reflection loss is -21.06dB at 15.84GHz, and the effective absorption bandwidth is 2.72GHz; Figure 5 It can be seen that as the thickness changes, the performance also changes.

[0074] For composite materials with MXene-FePc material (MXene to FePc mass ratio is 1:2) as filler and PVDF as substrate:

[0075] (1) When the filling amount is 10wt%, the corresponding thickness is 4.50mm, the minimum reflection loss is -39.66dB at 17.36GHz, and the effective absorption bandwidth is 1.60GHz; Figure 6 It can be seen that as the thickness changes, the performance also changes.

[0076] (2) When the filling amount is 15wt%, the corresponding thickness is 4.50mm, the minimum reflection loss is -36.64dB at 16.08GHz, and the effective absorption bandwidth is 1.76GHz; Figure 6 It can be seen that as the thickness changes, the performance also changes.

[0077] (3) When the filling amount is 20wt% and the corresponding thickness is 4.00mm, the minimum reflection loss is -27.71dB at 15.84GHz, and the effective absorption bandwidth is 1.84GHz; Figure 6 It can be seen that as the thickness changes, the performance also changes.

[0078] Example 3

[0079] A MXene-loaded CuPc composite material is prepared based on a self-assembly method in this embodiment.

[0080] The method is:

[0081] S1. 0.4 g MXene powder was dissolved in 200 mL deionized water, 0.5 M NaOH solution was added, magnetic stirring was performed for 4 h, MXene was functionalized, and then solid-liquid separation was performed;

[0082] S2. When the mass ratio of MXene to CuPc is 1:4, 0.24 g of CuPc is dissolved in 240 mL of DMF, and dispersed by ultrasound or a cell crusher to obtain a CuPc solution; when the mass ratio of MXene to CuPc is 1:2, 0.28 g of CuPc is dissolved in 280 mL of DMF, and dispersed by ultrasound or a cell crusher to obtain a CuPc solution;

[0083] S3. When the mass ratio of MXene to CuPc is 1:4, 0.06 g of the functionalized MXene is dissolved in 60 mL of DMF, and the CuPc solution obtained in S2 is added dropwise to the MXene solution, and after ultrasonic dispersion, it is magnetically stirred for 20 hours under an argon atmosphere to obtain a uniform solution; when the mass ratio of MXene to CuPc is 1:2, 0.14 g of the functionalized MXene is dissolved in 140 mL of DMF, and the CuPc solution obtained in S2 is added dropwise to the MXene solution, and after ultrasonic dispersion, it is magnetically stirred for 20 hours under an argon atmosphere to obtain a uniform solution;

[0084] S4. The S3 solution is washed with DMF and deionized water, and freeze-dried to obtain a composite material.

[0085] The SEM image of the functionalized MXene prepared in step S1 of this embodiment is as follows: Figure 1 As shown in the figure, after the MXene is modified, the nanosheets curl and wrinkle to form a three-dimensional petal-like structure. Due to stacking, the size is further increased. This curling and stacking are beneficial to the construction of a conductive network.

[0086] The SEM image of the composite material prepared in step S4 of this embodiment is as follows: Figure 2 As shown in Figure c, MXene still retains the wrinkled morphology and larger size after functionalization, and CuPc is successfully loaded on MXene.

[0087] This embodiment also provides a composite material of the MXene loaded with CuPc and a polymer matrix prepared above. The obtained MXene-metal phthalocyanine composite material is used in a wave absorbing material: the MXene-metal phthalocyanine composite material and the matrix are mixed in a predetermined ratio, dispersed in an organic solvent, and ultrasonically mixed to obtain a uniform solution; the mixed solution is transferred to a glass evaporating dish, dried (preferably at 80°C) to remove the solvent to obtain a uniformly dispersed composite film, and then the film is placed in a mold for hot pressing to obtain the wave absorbing composite material. Its wave absorbing performance diagram is shown in FIG. Figure 7 and Figure 8 shown.

[0088] For composite materials with MXene-CuPc material (MXene to CuPc mass ratio of 1:4) as filler and PVDF as substrate:

[0089] (1) When the filling amount is 10wt% and the corresponding thickness is 4.50mm, the minimum reflection loss is -35.57dB at 5.12GHz, and the effective absorption bandwidth is 2.80GHz; Figure 7 It can be seen that its performance changes as the thickness changes;

[0090] (2) When the filling amount is 15wt% and the corresponding thickness is 5.00mm, the minimum reflection loss is -22.79dB at 4.32GHz, and the effective absorption bandwidth is 2.00GHz; Figure 7 It can be seen that its performance changes as the thickness changes;

[0091] (3) When the filling amount is 20wt% and the corresponding thickness is 1.75mm, the minimum reflection loss is -29.96dB at 10.48GHz, and the effective absorption bandwidth is 2.24GHz; Figure 7 It can be seen that as the thickness changes, the performance also changes.

[0092] For composite materials with MXene-CuPc material (MXene to CuPc mass ratio of 1:2) as filler and PVDF as substrate:

[0093] (1) When the filling amount is 10wt%, the corresponding thickness is 3.50mm, the minimum reflection loss is -39.98dB at 5.68GHz, and the effective absorption bandwidth is 1.28GHz; Figure 8 It can be seen that as the thickness changes, the performance also changes.

[0094] (2) When the filling amount is 15wt%, the corresponding thickness is 1.27mm, the minimum reflection loss is -42.96dB at 12.56GHz, and the effective absorption bandwidth is 2.40GHz; Figure 8It can be seen that as the thickness changes, the performance also changes.

[0095] (3) When the filling amount is 20wt% and the corresponding thickness is 1.50mm, the minimum reflection loss is -14.00dB at 8.16GHz, and the effective absorption bandwidth is 1.04GHz; Figure 8 It can be seen that as the thickness changes, the performance also changes.

[0096] The above is only an example of the embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for constructing a microwave absorbing material by loading metal phthalocyanine with MXene, characterized in that: The following steps are involved: S1. Functionalization of MXene with alkaline solution; S2. The metal phthalocyanine powder is mixed with the first solvent and dispersed to obtain a dispersed metal phthalocyanine solution; the dispersed metal phthalocyanine solution is mixed with the functionalized MXene dispersion solution to obtain a uniform solution of MXene and metal phthalocyanine; S3. The MXene and metal phthalocyanine homogeneous solution are ultrasonically mixed under an argon atmosphere, and a MXene-metal phthalocyanine composite solution is obtained by magnetic stirring reaction; S4. Filter and wash the MXene-metal phthalocyanine composite solution, and dry it to obtain a composite material.

2. The method according to claim 1, characterized in that S1 is preferably: mixing a few-layer MXene with an alkaline solution to obtain an alkaline solution of MXene; stirring the alkaline solution of MXene under an argon atmosphere, and then separating to obtain a functionalized MXene; The alkali is at least one of potassium hydroxide and sodium hydroxide; the concentration of the alkali solution is 0.125-1.000 mol / L, preferably 0.5 mol / L, and the functionalization time is 2-12 h.

3. The method according to claim 1, characterized in that The first solvent described in S2 is selected from DMF; the functionalized MXene dispersion solution uses the first solvent as a dispersion solvent; in S2, the metal phthalocyanine solution is dispersed using ultrasound or a cell crusher, and the dispersion time is 10 to 60 minutes.

4. The method according to claim 1, characterized in that The metal phthalocyanine central metal described in S2 is one or more of Fe, Co, Ni, Cu, Zn, Mn, and Pb.

5. The method according to claim 1, characterized in that The mass ratio of MXene to metal phthalocyanine in S2 is 1:1 to 1:

9.

6. The method according to claim 1, characterized in that In S3, the metal phthalocyanine solution is mixed with the MXene solution by dropwise addition, and the reaction is carried out at room temperature, with a magnetic stirring speed of 300 to 600 r / min and stirring for 10 to 30 h; In the MXene-metal phthalocyanine composite solution in S3, the mass percentage of MXene in the composite solution is 5% to 50%; S4 uses a centrifugal washing method with a rotation speed of 3000 to 10000 rpm.

7. A MXene-metal phthalocyanine composite material prepared according to the method described in any one of claims 1 to 6.

8. Application of the MXene-metal phthalocyanine composite material prepared by the method according to any one of claims 1 to 6 in the field of wave absorption.

9. A microwave absorbing composite material, characterized in that: The MXene-metal phthalocyanine composite material prepared by the method according to any one of claims 1 to 6 and the matrix are composited to prepare an absorbing composite material, wherein the mass ratio of the MXene-metal phthalocyanine composite material to the matrix is ​​(0.1 to 0.4):1; The matrix is ​​selected from at least one of paraffin, resin and polyvinylidene fluoride.

10. The method for preparing the wave absorbing composite material according to claim 9, characterized in that: The following steps are involved: (1) mixing the MXene-metal phthalocyanine composite material and the matrix in a predetermined ratio, dispersing them in an organic solvent, and ultrasonically mixing them to obtain a uniform solution; the organic solvent is at least one of N,N-dimethylformamide (DMF) and n-hexane; (2) transferring the mixed solution to a glass evaporating dish, drying (preferably at 80° C.) to remove the solvent to obtain a uniformly dispersed composite film, and then placing the film in a mold for hot pressing to obtain the absorbing composite material, wherein the film thickness of the obtained composite material is in the mm level; The absorbing frequency band is controlled by adjusting the dosage relationship of MXene and metal phthalocyanine, the dosage relationship of MXene-metal phthalocyanine composite material and matrix, and the thickness of the film. The generally controlled absorbing frequency band ranges from 2 to 18 GHz.

Citation Information

Patent Citations

  • Preparation method and application of MXene quantum dot loaded phthalocyanine molecule composite catalyst

    CN114318369A

  • Composite wave-absorbing material prepared by deriving MXene / heterogeneous metal MOFs and method thereof

    CN116751562A

  • Rock stratum-shaped Co3Fe7 alloy-coated TiO2 / C composite material as well as preparation method and application thereof

    CN117239434A

  • Multilayer TiN / iron phthalocyanine composite material electrocatalyst and preparation method and application thereof

    CN117594809A

  • Oxidation-resistant rare earth transition magnetic composite material and preparation method thereof

    CN118338641A